DEVELOPING ENGLISH SUPPLEMENTARY MATERIAL FOR NARRATIVE TEXT BASED ON WRITING TASK FOR TENTH GRADE OF ELECTRICAL POWER INSTALLATION PROGRAM IN SMK ISLAM 1 BLITAR - Fikrima Sinta Nuriyah; Ahmad Saifudin; Tyas Alhim Mubarok (IKIP Siliwangi, 2023)
The government, through the Ministry of Education and Culture, seeks to provide teaching materials (text books) and revise the 2013 Curriculum, which distinguishes it from the High School English Curriculum, in order to fulfill good English language skills in students, especially in Vocational High Schools. Media in learning English is very important, as evidenced by an analysis of the needs of 38 students and an English teacher of class X Grade in the Electrical Power Installation Program. This study aims to determine the process of obtaining English teaching materials needed by students and the development of English supplementary material for narrative text based on the writing task. This study used the ADDIE Research and Development model (R&D) model. The results used questionnaires, unstructured interviews, expert judgment, and observation. It used several steps including: (1) Research&Information collection, (2) Develop preliminary form of product, (3) Product revision, (4) Product testing, (5) Final product revision. The object of this research subject is research were 38 students of X Grade in Electrical Power Installation Program students majoring at SMK Islam 1 Blitar. The result of expert validation showed that the product gets a 3,89 value is in the range of 3.25 < x < 4. This supplementary material is categorized “Very Good” feasible to use as supplement about narrative text material for X Grade in Electrical Power Installation Program students majoring.